2013
DOI: 10.1177/0961203313499086
|View full text |Cite
|
Sign up to set email alerts
|

Chinese SLE Treatment and Research group (CSTAR) registry: I. Major clinical characteristics of Chinese patients with systemic lupus erythematosus

Abstract: The Chinese systemic lupus erythematosus (SLE) treatment and research group (CSTAR) provides major clinical characteristics of SLE in China and establishes a platform to provide resources for future basic and clinical studies. CSTAR originated as a multicentre, consecutive, and prospective design. The data were collected online from 104 rheumatology centers, which covered 30 provinces in China. The registered patients were required to meet four or more of the American College of Rheumatology (ACR) criteria for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
3
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(95 citation statements)
references
References 32 publications
5
86
3
1
Order By: Relevance
“…For instance, the prevalence of CNS lupus was 20% in this study, compared with 4.8% reported from a national registry study of ambulatory Chinese patients with SLE. 28 We speculate that Purtscher-like retinopathy is less common among ambulatory patients of SLE.…”
Section: Purtscher Retinopathy Was Initially Described Inmentioning
confidence: 99%
“…For instance, the prevalence of CNS lupus was 20% in this study, compared with 4.8% reported from a national registry study of ambulatory Chinese patients with SLE. 28 We speculate that Purtscher-like retinopathy is less common among ambulatory patients of SLE.…”
Section: Purtscher Retinopathy Was Initially Described Inmentioning
confidence: 99%
“…Based on the SLE patients registered in the CRDC, papers on basic demographic characteristics and first symptom in Chinese SLE patients [5], risk factors of pulmonary hypertension [8], correlations between autoantibodies and clinical manifestations [9], and factors related to fetal loss [10] have been published. The SLE patients in the study of Li et al showed differing primary symptoms [5], of which rash, arthritis, fever, cytopenia, and kidney disease were the most common. Comparisons of clinical phenotypes in different cohorts are shown in Table 2 [11][12][13][14][15].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, diagnosis and treatment standards for Chinese patients are needed to guide physicians in clinical practice and ensure better care for patients with rheumatic diseases. After receiving financial support from the National Science and Technology Support Project in 2009, Peking Union Medical College Hospital (PUMCH) launched the Chinese Systemic Lupus Erythematosus (SLE) Treatment and Research Group (CSTAR), initiated the research and development of the Chinese SLE Information System (CSIS) in collaboration with several other rheumatology centers in China, and established the national SLE registration standard and information-sharing mechanism among CSTAR members for follow-up and referral of patients to ensure the sustainability of research cohorts [5].…”
Section: Introductionmentioning
confidence: 99%
“…В насто-ящее время показана чувствительность пациентов как к УФА, так и к УФИ, подтвержден также факт обнаружения антител к ДНК, денатурированной ультрафиолетом, у больных СКВ. Солнечная инсо-ляция может как предшествовать развитию заболе-вания, так и вызывать экзацербацию [9][10][11][12][13][14][15]. При-водим собственное наблюдение.…”
Section: Abstract: Negative Effect Of Ultraviolet Irradiation Solariunclassified